Sexual origins of British Aspergillus nidulans isolates. - Geiser, D M (1994)
Aspergillus nidulans is a holomorphic fungus, capable of producing both meiotically and mitotically derived spores. Meiosis may be an evolutionary relic in this species because it is potentially capable of mitotic recombination and because most Aspergilli lack the ability to produce meiotic spores. We tested the null hypothesis that meiosis has been a major factor in the origin of strains of A. nidulans from Great Britain by estimating linkage disequilibrium among restriction fragment length polymorphisms. These strains belong to different heterokaryon compatibility groups and are thus incapable of undergoing mitotic recombination with one another, so any recombination evidenced by linkage equilibrium is assumed to be the result of meiosis. Eleven cosmid clones of known chromosomal origin were used to generate multilocus genotypes based on restriction-pattern differences for each heterokaryon compatibility group. Low levels of genetic variation and little linkage disequilibrium were found, indicating that the heterokaryon compatibility groups represent recently diverged lineages that arose via meiotic recombination. The null hypothesis that loci are independent could not be rejected. Additionally, low levels of electrophoretic karyotype variation were indicative of meiosis. We conclude that although A. nidulans probably propagates in a primarily clonal fashion, recombination events are frequent enough to disrupt the stable maintenance of clonal genotypes. We further conclude that the British heterokaryon compatibility groups arose via recombination and not through novel mutation.